Gender analysis is not only about gender: reshaping the potato breeding priorities to increase varietal adoption in Kenya - Friedmann, M.; Polar, Vivian; Mendes, T. (Frontiers Media, 2024)
Public breeding programs are pushing to implement demand-led breeding to increase variety adoption, while tackling multiple challenges for increased production under climate change. This has included the improvement of variety target product profiles involving multiple stakeholders. A special case involves the unexpected and rapid spread of the Shangi potato variety in Kenya. This variety was not an especially outstanding variety and the levels of its traits did not exceed the expected thresholds defined in the target product profile for table potato in East Africa. By examining the customer segments looking at gender but also social contexts of smallholder and disadvantaged farmers such as access to markets, inputs, and labor, it became apparent that ready availability of potatoes for consumption, processing, or planting was of prime importance. Given the storage and market constraints, Shangi's very short dormancy, which had been assumed to be a negative trait for farmers, women cottage processors and consumers, was actually meeting the needs for available product and planting material. Consequently, this provided these groups increased control over their productive activities. The case study presented here analyzes different components of potato variety change in Kenya. It explores the challenges and tradeoffs faced by public sector breeding programs and how gender analysis from a broader inclusion perspective can uncover the underlying causes of varietal adoption. Focusing on the Shangi potato variety, the case study reveals a series of lessons learned that have re-shaped the definition of breeding priorities.